PEMANFAATAN AIR LIMBAH PRODUKSI BETON READY-MIX SEBAGAI BAHAN CAMPURAN UNTUK PEMBUATAN BETON BARU - Slamet Widodo (Universitas Negeri Yogyakarta, 2010)
Production of large amounts of waste wash water coming from ready-mixedconcrete plants leads to problems of environmental impact. Well developed countries usually prohibit the disposal of such types of water, due to their extremely high pH value and suspended matter amount, and require the water to be treated prior to discharge. prEN 1008 and ASTM C94 provide for recycling waste water in the production of new concrete, but gives some restrictions for its composition and use. In this paper, the use of waste washes water (coming from a medium-size ready-mixed concrete plant) in mixing water for concrete has been investigated, especially the effects on some mechanical and physical properties. The waste wash water used as partial replacement (0%, 25%, 50%, 75%, and 100% by volume) of the total water content. The experimental tests conducted on the 7-day and 28-day of compressive strength, water absorption, and the coefficient of sorptivity. The results have shown that some variants of concrete prepared with recycled water exhibit better 28-day compressive strength compared to the reference materials. The use of wash water inconcrete leads to a reduction of the water absorption and concrete sorptivity, which surely improves the durability of the material. The optimal use of waste wash water is 25% by total volume of the water content. This effect can be ascribed to the filling action of the fines present in the wash water and to the slight reduction of the actual water/cement ratio.Keywords: Waste Wash Water, Compressive Strength, Water Absorption, Sorptivity